2015
DOI: 10.1590/s0100-204x2015000400009
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade e mineralização do nitrogênio após aplicações sucessivas de lodo de esgoto no solo, estimadas por meio de incubação anaeróbica

Abstract: Resumo -O objetivo deste trabalho foi avaliar, por meio de incubação anaeróbica, a mineralização e a disponibilidade de N em solos tratados com aplicações sucessivas de lodo de esgoto, e determinar o efeito residual das aplicações anteriores na taxa de mineralização do nitrogênio (TMN). Dois experimentos de longa duração foram realizados com doses anuais de lodo de esgoto, para o cultivo de milho: um com dose recomendada de lodo, correspondente a 120 kg ha -1 de N, e 2, 4 e 8 vezes essa dose, em área da Embrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…similar to soil conditioners and organic fertilizers (Table 1). The evaluation of ASS indicated similar values to those found in literature for organic carbon (21-32%), nitrogen (1.09-4.2%), phosphorus (0.56-4.2%), calcium (3.42-3.82%), magnesium (0.14-1.93%), sulfur (0.89-2.68%) and manganese (120-400 mg kg − 1 ), however, the pH (5.4-7.9) and potassium content (0.2-1.5%) were lower than those previously found in the literature, while values for aluminum (0.76-1.64%) and iron (1.03-2.60%) were larger (Bueno et al, 2011;Stemann et al, 2015;Pires et al, 2015;Pesonen et al, 2016;Ren et al, 2015;Herzel et al, 2016;Kodešová et al, 2019). These differences were probably due to particularities in the anaerobic digestion process.…”
Section: Physicochemical Characteristics Of Acid Anaerobic Sewage Sludgementioning
confidence: 54%
“…similar to soil conditioners and organic fertilizers (Table 1). The evaluation of ASS indicated similar values to those found in literature for organic carbon (21-32%), nitrogen (1.09-4.2%), phosphorus (0.56-4.2%), calcium (3.42-3.82%), magnesium (0.14-1.93%), sulfur (0.89-2.68%) and manganese (120-400 mg kg − 1 ), however, the pH (5.4-7.9) and potassium content (0.2-1.5%) were lower than those previously found in the literature, while values for aluminum (0.76-1.64%) and iron (1.03-2.60%) were larger (Bueno et al, 2011;Stemann et al, 2015;Pires et al, 2015;Pesonen et al, 2016;Ren et al, 2015;Herzel et al, 2016;Kodešová et al, 2019). These differences were probably due to particularities in the anaerobic digestion process.…”
Section: Physicochemical Characteristics Of Acid Anaerobic Sewage Sludgementioning
confidence: 54%
“…The highest GY found for the cultivars under residual fertilization of sewage sludge was attributed to the improvement of soil chemical and physical characteristics, mainly by the increase in organic matter and decrease in soil density (Table 3), which contribute for higher availability of nutrients, especially nitrogen, since this element limits cowpea grain yield because it is the most extracted nutrient by the crop (TAGLIAFERRE et al, 2013). The nitrogen in the sewage sludge is predominantly organic (PIRES et al, 2015), and is gradually mineralized over time and made available to plants (ZARE; RONAGHI, 2019). Thus, nitrogen can be kept longer in soils fertilized with sewage sludge than in soils fertilized with high-solubility fertilizers, which results in increases in grain yield.…”
Section: Resultsmentioning
confidence: 99%
“…Siqueira et al [24] found that in soil under NT system for 12 and 22 years, the averages for N mineralization were 0.19 and 0.26 g m −2 day −1 , respectively. For organic compounds such as sludge, the N mineralization rate is generally below 50%, 5-38% [25], 14-43% [26], 7-16% [27], and 24-31% [28]. Among the species used in straw production, Fabaceae plants stand out for fixing atmospheric N 2 and presenting low C/N ratio tissues, in addition to the high soluble compound content and low lignin and polyphenol contents.…”
Section: Nitrogen Mineralization and Immobilization In The Agriculturmentioning
confidence: 99%